Uji Efektivitas Herbisida Pasca Tumbuh Pada Tanaman Kedelai (Glycine max. L): Post-Growing Herbicide Effectiveness Test on Soybean Plants (Glycine max. L) - Indarwati, Indarwati; Thohiron, Mochamad; Triyono, M. Fajri (Journal of Applied Plant Technology, 2022)
The purpose of this study was to determine the effect of weed control with herbicides on soybean growth and yield. This research was conducted in the Mojosari Agricultural Experimental Garden, Mojokerto, March - July 2021. The method used was a Randomized Block Design (RAK) with 3 treatments and 4 replications. The treatments were (P0) mechanical weeding (Control); (P1) Spraying herbicide 1X; (P2) spraying. 2X herbicide. selective herbicide spraying (Agil 100 ec) with the active ingredient propaquzafop 100 ec C-12 was carried out according to the treatment. Herbicide application had a better effect on soybean yields than control (mechanical weeding). However, spraying herbicides once had the same good effect as (P2) spraying 2X. The soybean plants tested were able to produce dry pods weight of 36.85 -39.00 g/plant, and dry weight 100 seeds 18,48-20,90 g.